Endocrine Disorder in Patients With Craniopharyngioma - Zhou, Zihao; Zhang, Sheng; Hu, Fangqi (Frontiers in Neurology, 2021)
Craniopharyngioma is an intracranial congenital epithelial tumor growing along the pathway of the embryonic craniopharyngeal tube. The main clinical symptoms of craniopharyngioma patients include high intracranial pressure, visual field defect, endocrine dysfunction, and hypothalamic dysfunction. At present, the preferred treatment remains the surgical treatment, but the recovery of endocrine and hypothalamic function following surgery is limited. In addition, endocrine disorders often emerge following surgery, which seriously reduces the quality of life of patients after operation. So far, research on craniopharyngioma focuses on ways to ameliorate endocrine dysfunction. This article reviews the latest research progress on pathogenesis, manifestation, significance, and treatment of endocrine disorders in craniopharyngioma patients.